2021
DOI: 10.3390/toxics9070164
|View full text |Cite
|
Sign up to set email alerts
|

A Multidisciplinary Approach for the Assessment of Origin, Fate and Ecotoxicity of Metal(loid)s from Legacy Coal Mine Tailings

Abstract: Over the course of history, the development of human societies implied the exploitation of mineral resources which generated huge amounts of mining wastes leading to substantial environmental contamination by various metal(loid)s. This is especially the case of coal mine tailings which, subjected to weathering reactions, produce acid mine drainage (AMD), a recurring ecological issue related to current and past mining activities. In this study, we aimed to determine the origin, the fate and the ecotoxicity of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…For example, there is condensation of water vapor, resulting in low values of both hydrogen and oxygen isotopes with small slopes [45]. (6) Gibbs plot can be effectively analyzed by Na + / (Na + +Ca 2+ ) and Cl -/(Cl -+HCO 3 -) compared with TDS, respectively (Fig. 7).…”
Section: Sources Of Main Groundwater Componentsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, there is condensation of water vapor, resulting in low values of both hydrogen and oxygen isotopes with small slopes [45]. (6) Gibbs plot can be effectively analyzed by Na + / (Na + +Ca 2+ ) and Cl -/(Cl -+HCO 3 -) compared with TDS, respectively (Fig. 7).…”
Section: Sources Of Main Groundwater Componentsmentioning
confidence: 99%
“…Since the 1990s, with the closure of a large number of mines in Yunnan province, pit mine water may enter the adjacent soil-groundwater system, causing regional soil and groundwater pollution [4,5]. Pit water, washing wastewater and leaching water from waste heap produced during coal mine production are the main sources of soil and water pollution, resulting in the exceedance of S, Fe, Mn and other indicators in the water bodies around the mine catchment area, and a tight supply of safe domestic water in the mine catchment area [6].…”
Section: Introductionmentioning
confidence: 99%
“…The same authors, Antunes et al (2007) assessed the toxicity of sediment elutriates from artificial ponds from a uranium mine exploitation (with low pH and high concentration of PTE) using acute assays with D. magna and D. longispina (EC 50 = 96.3% and 94.7%, respectively). Gauthier-Manuel et al (2021) reported that after exposure to acid drainage from a coal mine, a growth inhibition and an emergence delay of model organism Chironomus riparius larvae were observed. On the other hand, biochemical biomarkers are frequently used to assess the effects of organisms' exposure to environmental contaminants (Lionetto et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…It is a heavy, non-essential metal and non-threshold neurotoxicant [ 17 , 20 ]. Although Pb is naturally present in the environment, today’s considerably high Pb levels in the environment are a direct consequence of the industrial revolution and rapid urbanization [ 18 , 21 , 22 , 23 ]. Despite national and international efforts to reduce Pb levels in the environment, it remains one of the greatest pollutants [ 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%